Beyond Fresh Fruit Bunch Aggregation: A Framework for Koperasi Desa/Kelurahan Merah Putih (Indonesia’s Village Cooperatives) in Advancing Oil Palm Smallholder Welfare in Indonesia - Loso Judijanto (Nomico, 2026)
Indonesia's Koperasi Desa/Kelurahan Merah Putih (KDKMP) initiative creates a new institutional opportunity to strengthen village economies, including in regions dominated by independent and scheme oil palm smallholders. Yet cooperative formation, physical infrastructure, and subsidised financing do not automatically improve member welfare. This qualitative literature review synthesises recent evidence on agricultural cooperatives, oil palm smallholders, collective action, rural finance, replanting, certification, digitalisation, and cooperative governance to identify the roles KDKMP should perform and the conditions required for those roles to generate durable welfare gains. The review finds that KDKMP should move beyond a narrow fresh fruit bunch aggregation model. Its welfare-enhancing functions should integrate transparent collective marketing, shared logistics, affordable and verified inputs, extension and farm records, savings and credit, replanting facilitation, land and business legality, group certification, traceability, livelihood diversification, and carefully staged local value addition. These functions can raise net income, stabilise cash flow, reduce transaction costs, improve productivity, and strengthen bargaining power only when supported by genuine member ownership, professional management, adequate working capital, auditable digital records, inclusive decision-making, viable partnerships, and safeguards against elite capture and excessive debt. The article proposes a four-stage maturity model and a balanced performance dashboard that prioritise member-level outcomes over the number of cooperative entities, buildings, assets, or business units. The central policy implication is that KDKMP should be governed as a member-owned rural economic platform whose expansion is conditional on demonstrated benefits, financial health, and institutional accountability.